Kajian Penanganan Bahan Baku Ikan Cakalang (Katsuwonus pelamis) Menjadi Produk Beku di PT X - Damayanti, Wa Ode Nelva; Anwar, Lely Okmawaty; Nurdiyanty, Iin; Rosmawati, Rosmawati; Tamtama, Ary (Fakultas Pertanian Universitas Muhammadiyah kendari, 2026)
Skipjack tuna (Katsuwonus pelamis) is a fishery commodity that is highly susceptible to quality deterioration, thus requiring proper handling to maintain product quality and food safety, particularly in frozen products. This study aimed to examine the conformity of raw material handling processes of skipjack tuna into frozen products at PT X based on the Indonesian National Standard (SNI). The study employed a qualitative descriptive method using gap analysis and a compliance-based scoring system approach. Data were collected through direct observation, interviews, and literature studies. The observed processing stages included raw material receiving, sorting, weighing, glazing or non-glazing, packaging (labeling), and storage. The results showed that all production process stages achieved a conformity level of 91,6 %, categorized as highly compliant with the SNI standards. Meanwhile, supporting materials obtained a conformity level of 75%, where the use of water met the required standards, while the use of ice was not fully compliant due to the unclear documentation of the water source used for ice production. In conclusion, the handling process of frozen skipjack tuna at PT X generally met the requirements of sanitation, quality, and food safety standards; however, improvements are still needed in the control of supporting materials.